Molecular characterization of Aster yellows (16SrI) group phytoplasma infecting Cannabis sativa in eastern Uttar Pradesh - MALL, SMRITI; RAO, G.P.; UPADHYAY, P.P. (Indian Phytopathology, 2011)
During survey of diseases of weeds in and around agricultural fields in eastern UP in 2008, non-specific yellowing, chlorosis of leaves, proliferation of axillary shoots and witches’-broom symptoms on Cannabis sativa plants followed by death of entire plants were recorded. Suspected infected and healthy tissues of C. sativa from different locations at Gorakhpur in eastern UP, India, were examined by nested PCR assay using universal phytoplasma primers P1/P6 and R16F2n/R16R2. C. sativa plant with non-specific yellowing and witches’-broom symptoms yielded phytoplasma-exclusive DNA bands of 1.2 kb when nested PCR was performed. BLAST search analysis of the 16S rRNA sequence of the C. sativa phytoplasma shared 99% identity with those of phytoplasma members of 16SrI group, ‘Candidatus Phytoplasma asteris’. Therefore, the C. sativa phytoplasma under present study was identified as a member of the 16SrI group.